A Development and Empirical Validation of The Consumer Response Towards Sponsored Search Advertising (SSA) Model (Global Journal of Management and Business Research, 2012)
Dramatic structural changes are taking place within the rapidly growing Web advertising sector; the most notable being the rise to prominence of Sponsored Search Advertising (SSA) which developed because of the need to find solutions to the increased market demand for more consumer-oriented and targeted advertising and non-intrusive Web Advertising format (Weidlich, 2002). Moreover, SSA offered advertisers the ability to more precisely target Web users, as well as making the advertisements more relevant and meaningful to the consumers (Dou et al., 2001). However, very little attention has been given to SSA in terms of how consumers respond to such advertising within the Web context, and what particular factors drive consumers to attend to, and respond to, SSA. To address this gap in the marketing literature, the current study sought to, firstly present a theoretical Model of Consumer Response Towards SSA by incorporating variables synthesized from the advertising and consumer behaviour literature. Secondly, this study empirically validated the model from the consumer#x2019;s perspective.
Keywords: Web Advertising; Sponsored Search Advertising; Consumer behaviour; Consumer attention; and Consumer attitudes